ANALISIS PERMOHONAN PRAPERADILAN TENTANG KEABSAHAN PENETAPAN STATUS TERSANGKA (STUDI PUTUSAN PRAPERADILAN NOMOR: 2/Pid.Pra/2021/ PN.Wat) - Anisya Noviana Hartono; Ismawati Septiningsih (Verstek, 2023)
This article aims to determine the compatibility between the reasons for submitting a pretrial request regarding the validity of determining the suspect's status in the Pretrial Decision Number: 2/Pid.Pra/2021/PN.Wat with the provisions of the Criminal Procedure Code and other provisions relating to pretrial. This research is included in normative legal research with a case approach. Types of legal materials consist of primary and secondary legal materials. The results of the research on the writing of this law show that the reason for submitting a pretrial request regarding the validity of determining the status of a suspect in the Pretrial Decision Number: 2/Pid.Pra/2021/PN.Wat is not in accordance with the provisions of the Criminal Procedure Code. However, this is in accordance with the provisions of the Constitutional Court Decision Number: 21/PUU-XII/2014 and Supreme Court Regulation Number 4 of 2016. This shows that the provisions regarding Pretrial in the Criminal Procedure Code are not perfect, so several additional regulations are needed to perfect them as contained in the Constitutional Court Decision Number: 21/PUUXII/2014 and Supreme Court Regulation Number 4 of 2016. Therefore, it is necessary to prepare pretrial procedural legal instruments in the form of a law that can ensure that the pretrial process can be carried out in a fair and accountable manner.